2007
DOI: 10.1073/pnas.0610222104
|View full text |Cite
|
Sign up to set email alerts
|

A dominant mutation in Snap25 causes impaired vesicle trafficking, sensorimotor gating, and ataxia in the blind-drunk mouse

Abstract: The neuronal soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex is essential for synaptic vesicle exocytosis, but its study has been limited by the neonatal lethality of murine SNARE knockouts. Here, we describe a viable mouse line carrying a mutation in the b-isoform of neuronal SNARE synaptosomal-associated protein of 25 kDa (SNAP-25). The causative I67T missense mutation results in increased binding affinities within the SNARE complex, impaired exocytotic vesicle recycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 49 publications
2
103
1
Order By: Relevance
“…PKC-mediated phosphorylation of SNAP-25 has been shown to increase SNAP-25-syntaxin binding (58), likely resulting in slower SNAP-25-syntaxin dissassembly, which has been suggested to interfere with complete SNARE complex formation, because a syntaxin molecule needs to be replaced by synaptobrevin for formation of the ternary complex (57). Enhanced SNAP-25-syntaxin binding might also hinder full docking of new granules at the IRP release sites, as has been suggested in the blind-drunk mouse, which has a mutation of SNAP-25b that leads to stabilization of the SNARE complex (24,61). SNAP-25 phosphorylation and increased SNAP-25-syntaxin binding may thus account for our hypothesis of decreased full docking rate after PKC activation.…”
Section: Discussionmentioning
confidence: 99%
“…PKC-mediated phosphorylation of SNAP-25 has been shown to increase SNAP-25-syntaxin binding (58), likely resulting in slower SNAP-25-syntaxin dissassembly, which has been suggested to interfere with complete SNARE complex formation, because a syntaxin molecule needs to be replaced by synaptobrevin for formation of the ternary complex (57). Enhanced SNAP-25-syntaxin binding might also hinder full docking of new granules at the IRP release sites, as has been suggested in the blind-drunk mouse, which has a mutation of SNAP-25b that leads to stabilization of the SNARE complex (24,61). SNAP-25 phosphorylation and increased SNAP-25-syntaxin binding may thus account for our hypothesis of decreased full docking rate after PKC activation.…”
Section: Discussionmentioning
confidence: 99%
“…From our experiments (Fig 2c), it was clear that anti-SNAP-25 reduced both the RRP (by ~45%) and refilling from the RP (~70%). Why the reduction by the SNAP-25 antibody is strongest during mobilisation remains to be answered, but it has earlier been shown that SNAP-25 is of importance for mobilisation of granules [18].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when Sørensen et al (26) separately overexpressed either SNAP-25a or SNAP-25b in embryonic adrenal chromaffin cells from SNAP-25-null mice, the burst of Ca 2+ -evoked catecholamine release differed. Furthermore, impairment of vesicle trafficking and reduced insulin secretion was observed in the blind-drunk mouse, a mutant with a dominant mutation in the SNAP-25b-specific exon, resulting in a further increased stability of the SNARE complex (47). Although SNAP-25a has a lower capacity to keep vesicles in a primed state, little is known how this molecular difference between the splice variants influences animal physiology.…”
Section: (E and F) Hypothalamic Pstat3 Is Decreased In All Experimentmentioning
confidence: 99%